Larung Sesaji at Ngebel Lake: Dialectics of ‘Urf with Local Culture from the Perspective of Ulama in Ponorogo, East Java - Al Jauhari, Shofwan; As'adah, Rifqi; Ahwani, Alyasura Maulana Zuvy; Solikhudin, Muhammad (LP2M - Universitas Islam Negeri Walisongo Semarang, 2024)
Traditions in religious life sometimes cause problems in society. The role of religious experts is very important in solving this problem. This study aims to analyze the tradition of larung Sesaji and the views of religious figures in Ponorogo regarding this procession. This study is qualitative research in which the data were collected from field research. For analysis, descriptive methods with a phenomenological approach are applied. The research results show that the tradition of larung sesaji in Ngebel Lake, with its various kinds of knick-knacks, is passed down from generation to generation as an accumulation of pre-Islamic customs. This tradition was originally a prayer for safety from the disaster caused by the supernatural ruler of Ngebel Lake. In response to this, the puritan Ulama in Ponorogo stated that larung sesaji is close to shirk (idolatry) and is considered ‘urf fāsid, so there is no need to practice it. While moderate ulama is more flexible, allowing the tradition to continue as usual while giving guidance so that any possibility of violations of the Shari’a can be anticipated; hence, it is considered ‘urf ṣaḥīḥ. However, as a consequence of the Constitutional Court Decision No. 97/PUU-XIV/2016 regarding believers with no belief to not include their religion on KTP (ID Card), people around Ngebel Lake have converted their faith (apostates). Eventually, this tradition and practice are beyond the authority of the MUI and ulama.